ALTERNATIVE MEDIA AND INTERNET: A QUALITATIVE ANALYSIS OF SPANISH MEDIA (Andamios, Revista de Investigación Social, 2009)
Internet has changed the social structure. Consequently, media have changed, too. This article is focused on Spanish online alternative media. In the Information Society, Internet has become the gateway to spread different news that would have been excluded in the mainstream media. Moreover, Internet permits new organizational structures in the newsrooms. However, the main conclusion of this article is to highlight that there is not a single model and ideology for online alternative media in Spain. On the contrary, there are different models and ideologies.
Keywords: Alternative media; alternative communication; internet; portal; spanish state